Customer Loyalty In Relation To Digital Marketing - Miranti Miranti; Masysyarah Nurul Pratiwi B.Koto; Andini Al Rasid (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Research The attitude of online customers regarding the deployment of digital marketing is one issue that impacts this study. Customer loyalty, brand recognition, and purchase choices make up the consumer's opinion on digital marketing implementation. In this study, there were 88 customers who actively utilized internet purchasing. They utilized SPSS 12 to do correlation analysis, t-tests, and F tests. This study found that brand awareness has a favorable and substantial impact on digital marketing implementation. Customer loyalty and purchase choices have a beneficial but not substantial impact on digital marketing deployment. The most prominent variable correlation test yields a correlation value of 0.774 for brand awareness, and 0.448 for customer loyalty and purchase choices. This research found that digital marketing can only be effective if consumer loyalty is maintained, the price is reasonable, the desired brand or brands are available, and there is a solid service system in place. As a consequence, customers will choose to continue utilizing digital marketing.